2002
DOI: 10.1038/sj.bjp.0704842
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide synthase inhibitors can antagonize neurogenic and calcitonin gene‐related peptide induced dilation of dural meningeal vessels

Abstract: 1 The detailed pathophysiology of migraine is beginning to be understood and is likely to involve activation of trigeminovascular a erents.2 Clinically e ective anti-migraine compounds are believed to have actions that include peripheral inhibition of calcitonin gene-related peptide (CGRP) release from trigeminal neurones, or preventing dural vessel dilation, or both. CGRP antagonists can block both neurogenic and CGRP-induced dural vessel dilation. 3 Nitric oxide (NO) can induce headache in migraine patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
159
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(171 citation statements)
references
References 35 publications
11
159
0
1
Order By: Relevance
“…11 Similarly, triptans can block meningeal vascular dilation, 28 a response that involves CGRP 7 and nitric oxide. 29 Studies that have used microiontophoresis have shown that BIBN 4096 BS blocks activity in the trigeminocervical complex of the cat that is induced by CGRP, l -glutamate, or stimulation of the superior sagittal sinus. 30 This effect is shared with ergot derivatives and triptans.…”
Section: Tolerability and Safetymentioning
confidence: 99%
“…11 Similarly, triptans can block meningeal vascular dilation, 28 a response that involves CGRP 7 and nitric oxide. 29 Studies that have used microiontophoresis have shown that BIBN 4096 BS blocks activity in the trigeminocervical complex of the cat that is induced by CGRP, l -glutamate, or stimulation of the superior sagittal sinus. 30 This effect is shared with ergot derivatives and triptans.…”
Section: Tolerability and Safetymentioning
confidence: 99%
“…CGRP injections trigger both migraine (Lassen et al, 2002) and dural vessel dilation (Williamson et al, 1997a) and CGRP antagonists have acute antimigraine properties (Olesen et al, 2003). NO is another known trigger of migraine (Dalsgaard-Nielsen, 1955;Thomsen et al, 1994) and dural vessel dilation (Akerman et al, 2002c). Both NO-induced dural vessel dilation (Akerman et al, 2002a) and headache (Iversen and Olesen, 1996) are affected by the antimigraine compound sumatriptan.…”
mentioning
confidence: 99%
“…Significance was assessed at the P Ͻ 0.05 level or below. The reproducibility of the neurogenic vasodilator response has been tested previously using four consecutive salinecontrolled stimuli (Akerman et al, 2002) in the same experimental setup.…”
Section: Discussionmentioning
confidence: 99%